Pengawasan Kementerian Agama dalam Pelaksanaan Perjalanan Haji dan Umrah di Kota Surakarta Tahun 2019 - Iklimatul Munawaroh (Solidaritas, 2022)
Supervision is carried out by the highest unit of the agency in all units under the auspices of the agency. Good supervision becomes a benchmark of the organization to achieve the target in carrying out surveillance activities, such as the supervision carried out by the Ministry of Religious Affairs at every Hajj and Umrah Travel Bureau in Surakarta City.This research aims to describe and analyze how is supervision carried out by the Ministry of Religious Affairs in the implementation of Hajj and Umrah travel in the city of Surakarta. This type of research uses a Qualitative Descriptive approach. Data collection techniques in other studies (1) interviews (2) observations (3) documentation. Data analysis techniques used are data collection, data condensation, data presentation and conclusion withdrawal. The results of this study show that the supervision carried out by the Ministry of Religious Affairs of Surakarta City in the regulation, licensing, reprimand, sanctions, and actions have been implemented properly. But in terms of socialization has not been implemented to the maximum. In addition, there has also been no supervision of branch bureaus in the city of Surakarta